APPLYING THE INTEGRATED CURRICULUM CONCEPT THROUGH CONNECTED MATHEMATICS PROJECT (CMP) LEARNERS TO MATHEMATICAL COMMUNICATION SKILLS - Isnani Isnani; Ruhban Masykur; Siska Andriani (Universitas Majalengka, 2021)
Based on the formulation of the problem above, this study has a goal to be achieved, namely: to determine the application of CMP learning to mathematical communication skills. To find out the concept of an integrated curriculum on mathematical communication skills. To find out whether there is an interaction between CMP learning and the concept of an integrated curriculum on mathematical communication skills. The experimenta type used in this study is Quasy Experimental Design. In this study, the sampling technique used was simple random sampling technique. To collect research data, there are several ways to use the data, including questionnaires anad tests. A good instrument must meet important requirements, namely validity test, difference power test, difficulty level and reliability test. Hypothesis testing uses the same two-way cell analysis. As for the results of this study, there in an influence between the CMP learning model and conventional learning on mathematical communication skills. There is no interaction between CMP learning and the integrated curriculum concept on mathematical communication skills. Keywords : concept curriculum integrated, connected mathematics project (cmp), mathematical communication skills